â€œBABAR LONTARâ€ STRATEGI GELIAT BUDAYA PELESTARIAN LONTAR DI BALI PADA MASA PENDEMI COVID-19 - Handana, Putu Dedi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The importance of knowing, studying, and disseminating the existence of lontar as a strategy to preserve ancestral heritage so that it can be a reference source for information related to previous human civilizations from various aspects of life, such as cultural, social, agricultural, medical, and so on, is very important. Efforts have been made to physically maintain the presence of lontar so that it is not easily damaged and can still be read as a source of cultural heritage. In the midst of the Covid-19 pandemic, all activities are starting to be limited, but active to disseminate the existence of lontar manuscripts is no longer a taboo thing but as something that must be known so that the perception of